Atividade antimicrobiana de extrato etanólico de própolis verde - Vilela, Camila de Oliveira (2010)
Propolis is a resinous substance by bees from exudates of flower-buds from several plants. Its coloring and consistancy is variable and it is used by bees to fill gaps, to embalm dead insects, as well as to protect the hive against the invasion of microorganisms. Green propolis, which has several bioactive proprieties scientifically proved, was evaluated in this study in the form of ethanolic extract, concerning its virucidal capacity against the avipoxvirus, inoculated in chorioallantoic membrane of chicken embryos and concerning its antibactericidal and antifungal action in embryonated eggs destinated to incubation. To evaluate the virucidal capacity of the Green própolis, 100 eggs embryonated were used, with nine days of incubation, of broiler breeders with 62 weeks of age, unvaccinated against avipoxvírus. Propolis presented virucidal activity depending on the dose and the time of vírus incubation period before the inoculation. Eggs inoculated with vírus and 2400 μg/dose of propolis previously incubated for four hours presented decrease in the number of lesion pox (P<0,05) with regard to the positive control besides a decrease in the number of bodies of intracytoplasmic inclusion and in the score of vacuolar degeneration of the epithelial cells of the mesoderm of the chorioallantoic membrane. After eight hours of vírus incubation the same propolis concentration inativated completely the avipoxvirus (P<0,0001) and a concentration ten times smaller (240 μ/dose) reduced significativelly the number of pox lesions and the histopathological findings (P<0,05). To evaluate the antibactericidal and antifungal activities of the ethanolic extract of the Green própolis, 140 eggs from nests of broiler breeders were used. The levels of contamination of eggshells through total mesophiles and fungi ( Aspergillus sp and other molds) after the desinfection with propolis were smaller as compared to the control. As compared to the treatment with formaldehyde (positive control) the concentrations of propolis 240 μg and 24 μg did not differ concerning the antibactericidal activity, but to the antifungal activity 2400 μg and 240 μg were superiors. Concerning the eggs hatchability after 21 days of incubation, the propolis treatmens (2400 μg and 240 μg) presented the biggest rates, with 94,11% overcoming the treatment with formaldehyde. Thus, the green propolis, presented virucidal activity against the avipoxvirus in chorioallantoic membrane, as well as antibactericidal and antifungal activity in embryonated eggs, representing a new alternative to treatments against infections caused by virus, as well as a new natural product disinfectant in substitution to formaldehyde.